Using artificial intelligence absolute beginner's guide - Miller, Michael 1958- (Pearson, 2025)
Artificial intelligence can be fun and productiveif you know which tools to use and when. Using Artificial Intelligence Absolute Beginners Guide tells you all about todays major AI tools and shows how to get the best results from them. Youll learn to use AI for turning your ideas into art, writing a great email, sharpening your resume, and even sparking conversation. Instantly research everything from planning a trip to making your next big purchase. Its all a matter of picking the right AI tool and constructing the right prompt. Youll also learn to protect yourself from the risks of AI and distinguish AI fakes from the real thing. Everything you need to know is here in this book!
Includes bibliographical references and index
Keywords: Artificial intelligence; Intelligence artificielle; artificial intelligence